`PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN WISATAWAN BERLIBUR DI KABUPATEN GAYO LUES - Muhammad Basyir; Maya Sari (Departemen Manajemen, 2019)
This study aims to determine and explain the influence of marketing mix on the decision of tourrists on vacation in Gayo Lues District. Variables that are used in this research consisted of product, place, price, and promotion towards decision of tour. The population in this study is tourists on tourism objects. Samples were taken as many as 100 respondents. Hypothesis testing use multiple regression analysis by using spss 16.0 for windows. The results showed that product, place and promotion significantly influence both simultaneously and partially on the decision of tour. This studi has limitations including the limited object of research and is expected in subsequent research to test different research objectis.